2003
DOI: 10.1136/thorax.58.7.567
|View full text |Cite
|
Sign up to set email alerts
|

Association of consumption of products containing milk fat with reduced asthma risk in pre-school children: the PIAMA birth cohort study

Abstract: Thorax 2003;58:567-572 Background: Environment and lifestyle contribute to the development of asthma in children. Understanding the relevant factors in this relationship may provide methods of prevention. The role of diet in the development of asthma in pre-school children was investigated. Methods: Data from 2978 children participating in a prospective birth cohort study were used. Food frequency data were collected at the age of 2 years and related to asthma symptoms reported at the age of 3 years. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
3
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(135 citation statements)
references
References 26 publications
4
122
3
4
Order By: Relevance
“…This result contrasts with that of a Swedish study involving 1014 schoolchildren (age 5-14 years), in which the associations between allergens and respiratory symptoms were more pronounced among those who did not consume butter and who had a low intake of milk (Kim et al, 2005). A similar observation was recorded in the Prevention and Incidence of Asthma and Mite Allergy birth cohort study (2003); after following 2978 pre-school children in the Netherlands for one year, the prevalence of recent asthma and wheezing was found to be lower in children who consumed butter daily than in those who did not (1.5 vs 5.1% for asthma and 7.7 vs 15.4% for wheezing) (Wijga et al, 2003). The authors of the latter study suggested that butter consumption increased the proportion of saturated fat in the diet and reduced that of unsaturated fat, and that a reduced proportion of linoleic acid in the diet might impede the development of asthma.…”
Section: Discussionsupporting
confidence: 51%
“…This result contrasts with that of a Swedish study involving 1014 schoolchildren (age 5-14 years), in which the associations between allergens and respiratory symptoms were more pronounced among those who did not consume butter and who had a low intake of milk (Kim et al, 2005). A similar observation was recorded in the Prevention and Incidence of Asthma and Mite Allergy birth cohort study (2003); after following 2978 pre-school children in the Netherlands for one year, the prevalence of recent asthma and wheezing was found to be lower in children who consumed butter daily than in those who did not (1.5 vs 5.1% for asthma and 7.7 vs 15.4% for wheezing) (Wijga et al, 2003). The authors of the latter study suggested that butter consumption increased the proportion of saturated fat in the diet and reduced that of unsaturated fat, and that a reduced proportion of linoleic acid in the diet might impede the development of asthma.…”
Section: Discussionsupporting
confidence: 51%
“…The reduction in atopy/ allergy risk among these studies ranged between 22 and 80%. It is important to note that two studies observed a negative effect of fish intake on childhood atopy (58,59) , and three studies observed no associations (60)(61)(62) . Studies of maternal fish oil supplementation during pregnancy report effects on umbilical cord blood immune markers (blood cytokine mRNA (63) , plasma cytokines (64) , LTB 4 production from neutrophils (65) , cytokine production by mononuclear cells (66) ) and an altered cord blood haemopoietic progenitor phenotype (67) .…”
Section: N-3 Pufa Eicosanoids and Inflammatory Processesmentioning
confidence: 99%
“…In particular, in childhood asthma a reduced maternal intake of vitamin E, vitamin D, selenium, zinc and PUFA has been invoked to explain the development of this allergic condition (4) . In this direction, two studies have suggested that dietary PUFA administration during pregnancy may reduce the likelihood of developing asthma (68,69) . However, further trials are required to confirm these results.…”
Section: Asthmamentioning
confidence: 99%